INCREASING POLITICAL AWARENESS THROUGH POLITICAL EDUCATION FOR WOMEN IN SAMBENG SUB-DISTRICT, LAMONGAN DISTRICT - Mimatun Nasihah (Sosio-Didaktika: Social Science Education Journal, 2018)
The title of its outreach program is the Increasing Political Awareness through Political Education for women in Sambeng Sub-district, Lamongan District. The objects of the activity were PKK members (a program at village level to educate women on various aspect of family welfare), female village heads, and female village secretaries in Sambeng sub-district. The objective of this outreach program was to elevate the understanding and awareness of the community for its role as a human or kholifah (leaders on earth), specifically the role of women in politics. The outcome of this program was to promote public understanding and awareness (especially women) in Sambeng District about political awareness for women. The method implemented was through Community Education namely educational activities used to elevate the perceptive and awareness of the community, especially political awareness for women. The conclusion of this outreach program was that the participants had limited understanding and awareness for the role and position of women in the family and in society (the state). The participants did not understand and were not aware of the political role it assumes as a kholifah on earth. In addition, the participants did not understand the procedures and mechanisms to become a representative of the people as members of the legislative council either. Therefore, the participants were very enthusiastic and asked many questions about how the religion viewed women who are actively involved in politics, how to balance family obligations with their social-political role, how to start engaging the political world if their husbands did not allow them, and the participants also asked how should be a capable and qualified board member.